- 1-800-665-6601
- info@tutorpace.com

3x + 4y = 10

2x + 3y = 5

3x + 4y = 10...................... (1)

2x + 3y = 5......................... (2)

First we need to multiply the given equation by a suitable number to make the coefficient of one variable equal.

Now we can plug this value in the equation 3x + 4y = 10

3x + 4 (-5) = 10

We can write this as x = 10

(x, y) = (10, -5)

-2x + y = 6

x + 2y = 2

-2x + y = 6...................... (1)

x + 2y = 2......................... (2)

First we need to multiply the given equation by a suitable number to make the coefficient of one variable equal.

y = 2

Now we can plug this value in the equation 2x + y = 6

-2x + 2 = 6

We can write this as x = -2

(x, y) = (-2, 2).